The variations of sentence structure in various question responses based on basic sentence patterns - Liusti, Siti Ainim; Zulfikarni, Zulfikarni; Bagea, Ishak; Ulya , Ridha Hasnul (BAHASTRA, 2026)
Syntactic competence is foundational to children’s literacy development; however, empirical research on how elementary learners construct sentences in response to specific interrogative prompts remains limited in Indonesian linguistic scholarship. Although prior studies have normatively described canonical sentence patterns or assessed general syntactic complexity, few have investigated the structural variations elicited by different question words. This study describes and analyzes the syntactic variations produced by fourth-grade students in response to five Indonesian interrogatives (where, how, who, why, what) and maps these responses onto the six canonical sentence patterns of Indonesian. Using a qualitative descriptive design and content analysis, the study examined students’ written responses to a narrative reading comprehension task. Each answer was parsed for syntactic function and evaluated against the framework of Standard Indonesian Grammar. Trustworthiness was ensured through thick description and inter-analyst triangulation. The findings reveal that each interrogative elicits a distinct range of syntactic realizations: full, elliptical, and compound with why producing the most elaborate, multi-clausal constructions. All observed variations align systematically with the six canonical patterns, indicating that ellipsis functions as a pragmatically motivated strategy rather than a syntactic deficiency. This study enriches the descriptive understanding of Indonesian child syntax and provides a diagnostic tool for elementary language instruction.